Pengaruh Pembelajaran Multi-Method Terhadap Minat Belajar Fisika dan Kemampuan Analisis Murid - Rahmayanti, Rahmayanti; Abdullah, Helmi; Palloan, Pariabti (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the effect of implementing a multi-method learning approach on students' physics learning interest and analytical skills. This quantitative research utilized an experimental design involving two sample groups of eleventh-grade students at UPTD SMA Negeri 1 Tapango. The experimental group (N = 30) was taught using the multi-method strategy, while the control group (N = 30) received a single-model approach (nonmulti-method). Data were gathered through analytical ability tests and learning interest questionnaires, which were then analyzed using descriptive and inferential statistics (paired samples t-test) via SPSS software. The descriptive analysis revealed that post-treatment, the Multi-Method group achieved a remarkably high mean score of 94.30 for both learning interest and analytical ability, demonstrating strong data homogeneity (S = 4.15; S2 = 17.18). This outcome significantly surpassed the Non multi-method group, which only obtained a mean score of 80.43 with more heterogeneous data distribution (S = 5.18; S2 = 26.81). Furthermore, inferential testing via the paired samples t-test confirmed that the multi-method intervention exerted a highly substantial and statistically real acceleration effect (p < 0.001) on both dependent variables. The negative values in the mean differences for learning interest (-19.700) and analytical capacity (-31.500) robustly substantiate the massive score enhancement from pretest to posttest within the experimental class. Based on these findings, it is concluded that multi-method learning is empirically effective in boosting physics learning interest while simultaneously optimizing students' analytical skills compared to the conventional single approach.